Differences In Lowering Blood Pressure Between Giving Infusa Of Salam Leaf (Syzyguim Polynatum) And Infusa Of Herba Celery (Apium Graviolens L) In Hypertension Patients To Pregnant Women At Puskesmas Balaraja - Meilda Setya Mustika Devi; Dede Sri Mulyana (CV. Inara, 2024)
Elevated blood pressure is a major factor for coronary and ischemic heart disease and hemorrhagic stroke, in addition to peripheral vascular disease, kidney disorders, retinal hemorrhages and visual disturbances. The aim of this study was to compare the level of effectiveness in reducing blood pressure in pregnant women who experience hypertension at the Balaraja Health Center by giving infusions of bay leaves (Syzygium polyanthum) and infusions of celery herb (Apium graveolens). This type of research is a quantitative research with the type of experimental method in this study is to compare the effectiveness of the infusion of bay leaves and celery leaves to lower blood pressure in pregnant women with hypertension. The results of this study indicate that there is a significant effect between giving bay leaf infusion to pregnant women with hypertension at Balaraja Health Center with an odds ratio of 0.667. and there is a significant effect between giving celery leaf infusion to pregnant women with hypertension at the Balaraja Health Center with an odds ratio of 1,500.